Numerical Simulation of the Effect of Pre-Strain on Fatigue Crack Growth in AA2024-T351 - Diogo M. Neto; Edmundo Sérgio; André Agra; Fernando V. Antunes (Metals)
The objective here is to study the effect of pre-strain on fatigue crack growth (FCG) in 2024-T351 aluminum alloy. Three pre-strain conditions were considered: without pre-strain, compressive and tensile permanent pre-strains of 4%. A numerical approach based on cumulative plastic strain at the crack tip was followed to predict FCG rate. The compressive pre-strain increased FCG rate, while the tensile pre-strain reduced the da/dN relative to the situation without pre-strain. The influence of pre-strain was linked with plasticity-induced crack closure. In fact, a linear trend was obtained between da/dN and ΔKeff for three crack lengths (a = 16.184; a = 15.048 mm and a = 15.152 mm) and three pre-strain conditions. The increase in the stress ratio from R = 0.1 to R = 0.5 and the elimination of the contact of crack flanks significantly reduced the effect of pre-strain, also pointing to the huge relevance of crack closure in this context. Finally, the effect of pre-strain on da/dN after an overload was also explained by crack closure variations.